Colonoscopy Finding: Pseudomembranous Colitis in Chronic Kidney Disease Patient - Febrianti, Ety; Vidi Orba Busro; Suyata (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Gastrointestinal symptoms are common among patients with chronic kidney disease, reported in up to 70%–80% of patients with end-stage kidney disease. Several factors are involved in the pathogenesis, including the accumulation of uremic toxins and intestinal flora changes. Pseudomembranous colitis is a manifestation of severe colonic disease that is usually associated with Clostridium difficile infection but can be caused by a number of different etiologies. Pseudomembranous colitis occurs when changes in the fecal flora allow Clostridium difficile overgrowth. Gut dysbiosis, an alteration of the composition and function of gut microorganisms, is commonly seen in patients with chronic kidney disease. Case presentation: This scientific report presents a case study of a 31-year-old woman diagnosed with pseudomembranous colitis and end-stage chronic kidney disease on hemodialysis. The colonoscopy showed yellow-white nodules that formed pseudomembranes, which were scattered between the edematous mucosa. The patient had been treated with metronidazole for 4 days, but there were side effects. The antibiotic was switched to meropenem for 6 days based on feces culture. The evaluation of colonoscopy result was normal. Conclusion: Pseudomembranous colitis is an inflammatory bowel condition most commonly caused by Clostridium difficile infection. The presence of pseudomembranous visualization in colonoscopy can significantly establish the diagnosis.